The Influence of Situational Leadership and Organizational Culture Moderated by Compensation on Employee Performance - Afandy, Moh; Setiawan, Margono; Hapsari, Raditha Dwi Vata (Interdisciplinary Social Studies, 2022)
The development of the retail business is quite rapid and followed by very fierce competition , causing PT Midi Utama Indonesia Tbk. Palu Branch needs to maintain a competitive advantage to remain competitive with other companies. Employees become one of the important resources to maintain a competitive advantage. Therefore, improving employee performance is required at all times, where changes occur so quickly and are difficult to predict. This study aimed at analyzing the influence of  situational leadership and organizational culture moderated by compensation on  employee performance. Respondents in this study were 108 office employees using the saturated sample technique (Census) in determining the sample. The data collection method uses a questionnaire and is analyzed using SEM-PLS. The results of this study show that situational leadership has an insignificant positive direct influence on employee performance. Likewise, the effect of a positive interaction is insignificant between compensation and situational leadership on employee performance. Meanwhile, organizational culture has a positive and significant effect directly on employee performance. The effect of the interaction of compensation and organizational culture proved to be positive and significant in influencing employee performance. The company is expected to maintain a clan culture that prioritizes teamwork and collaborativeity. Furthermore, the application of more flexible leadership according to the conditions and situations faced by the company needs to be optimized. In the end, the provision of indirect financial compensation needs to be improved so that it can strengthen the improvement of employee performance.